Political Issue Content in Talk Shows of Iraqi Islamic Party Satellite Channels: An Analytical Study - Abbas, Hussein Amir; Mustaf, Adel Adbulrazaq (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to explore the content of political issues presented in talk shows broadcast by Iraqi Islamic party satellite channels, with a focus on the priorities adopted by these programs in addressing political issues and identifying the main thematic axes used in discussing topics related to the issues raised. Methodology: The study adopted a descriptive approach based on the analytical survey method. A sample from a three-month programming cycle was selected, including the programs “Ala Al-Mastara” on Al-Furat Channel and “Before Tomorrow” on Al-Ahd Channel. The analysis focused on episode content in order to identify treatment priorities and key themes. Results: The findings indicate that the most frequently discussed issues were presidential nominations, political dialogue initiatives, political consensus, center–region relations, and political détente. Conversely, issues such as forming a political majority government, calls to dissolve parliament, holding early elections, and popular movements received less attention. The results also show that priority in addressing issues was often given to highlighting the role of officials and favoring one party over another, which affected the course of discussions. Regarding thematic approaches, the two programs adopted different strategies: “Ala Al-Mastara” focused on ongoing issues extended from previous episodes and used as references for subsequent ones, while “Before Tomorrow” emphasized emergent events as top-priority discussion topics. Conclusion: The study concludes that talk shows on Iraqi Islamic party satellite channels prioritize political issues based on the interests of the media outlet and the urgency of topics, with differing strategies between programs in following continuous issues versus focusing on emergent events. This reflects the impact of media programming on shaping the nature of political dialogue presented to viewers.